KARAKTERISTIK PERTUMBUHAN DAN HASIL PADI (Oryza sativa L.) AKIBAT PERLAKUAN BAHAN ORGANIK DAN PUPUK HAYATI - Endang Kantikowati, Yudi Yusdian, Karya, Dian Murti Minangsih, dan Rulia Rabiatul Alia (Program Studi Agroteknologi Faperta UNIBBA, 2022)
This study aims to determine the interaction between doses of organic matter and biological fertilizers on the growth and yield of rice (Oryza sativa). above sea level. The average rainfall is 2,417.4 mm/year and includes type C3 rainfall according to Oldeman. The study used a factorial randomized block design (RAK) method with 3 replications. The first factor is the dose of organic matter (K) which consists of 3 levels of treatment, namely: k1 = 0 tons/ha of organic matter k2 = 5 tons/ha of organic matter k3 = 10 tons/ha of organic matter. The second factor is the concentration of biological fertilizers (H) which is divided into 3 levels of treatment, namely: h1 = 0 ml/l biological fertilizers h2 = 2 ml/l biological fertilizers h3 = 4 ml/l biological fertilizers. The results showed that the treatment dose of organic matter and concentration of biological fertilizers did not interact on all parameters observed. Dosage of 10 tons/ha of organic matter gave a better effect on plant height at 40 DAP. Giving the concentration of biological fertilizer 4 ml/l gave a better effect on the parameters of dry milled grain.